Tallying differences between demographic subgroups from multiple institutions: the practical utility of nonparametric analysis. Issue 2 (3rd April 2017) - Yorke, Mantz
Abstract : When analysing course-level data by subgroups based upon some demographic characteristics, the numbers in analytical cells are often too small to allow inferences to be drawn that might help in the enhancement of practices. However, relatively simple analyses can provide useful pointers. This article draws upon a study involving a partnership with 13 UK universities to illustrate a relatively simple methodology that is more widely generalisable.